Model Manajemen Fundraising Wakaf - Miftahul Huda (Universitas Islam Negeri Jakarta, 2013)
Abstract: Waqf Fundraising Management Model. This article examines models of fundraising through conventional sources, waqf asset productivity at The Al-Falah Social Fund Foundation (YDSF) in Surabaya. This study shows that YDSF uses waqf fundraising management through developing a resource fundraising model such as fundraising method from conventional sources either directly or indirectly as well as grant fundraising model such as strengthening empowerment program on the distribution of endowments. Whereas in developing asset fundraising model and, in-kind waqf, YDSF has not yet developed such a model. Hence the YDSF uses merely the direct cluster management.Keywords: ṣadaqah jāriyah, al-ḥabs, charitable fundraising management, corporate social responsibilityAbstrak: Model Manajemen Fundraising Wakaf. Artikel ini mengkaji model fundraising wakaf melalui sumber-sumber konvensional, produktivitas aset wakaf, dan in-kind wakaf pada Yayasan Dana Sosial Al-Falah (YDSF) Surabaya. Studi ini menunjukkan bahwa Yayasan ini menggunakan manajemen fundraising wakaf dengan mengembangkan model resource fundraising seperti metode penggalangan dari sumber-sumber konvensional baik secara langsung maupun tidak langsung dan model grant fundraising seperti penguatan program pemberdayaan pada penyaluran wakaf. Sedangkan dalam pengembangan model asset fundraising, dan in-kind wakaf, YDSF belum dapat mengembangkannya sehingga YDSF termasuk nādhir wakaf yang masih dalam kluster pengelolaan wakaf langsung.Kata Kunci: ṣadaqah jāriyah, al-ḥabs, manajemen fundraising wakaf, corporate social responsibility